Spotlight on graduate student: Saiful Nizam Tajuddin, PhD (industrial chemistry)candidate - M. M., Yusoff; Saifful Kamaluddin, Muzakir; Nurul Nadia, Abd Razak; Muhammad Najib, Muhammad Nor (Penerbit UMP, 2009)
Saiful Nizam Tajuddin, 32 years old, was born in Kuantan. The son of a Navy man, Saiful Nizam himself spent the Iatter port of his schooling years at the Royal Military College.